0
$\begingroup$

I have this equation $$(1-P_x) = (1-P_y)^{127} + 127P_y(1-P_y)^{126}$$

now I have $P_y=0.125*10^{-3}$
I've tried to solve $P_x$ using logarithms but I'm doing something wrong since $P_x$ cames out negative $$ log(1-P_x) = 127log(1-P_y)[log(127)+log(P_y)+126log(1-P_y)] $$ then i calculate $10^{log(1-P_x)}$ and i find $P_x$ but it's negative!

$\endgroup$
3
$\begingroup$

Rewrite

\begin{align*} (1-P_x) &= (1-P_y)^{127} + 127P_y(1-P_y)^{126}\\ &= (1-P_y)^{126}(1-P_y + 127P_y) \end{align*}

Now we may take the logarithm.

$\endgroup$
2
$\begingroup$

When you've taken logs initially, you appear to have used the 'fact' that $$\log(a+b)=\log(a)\log(b)$$ Unfortunately this is not true e.g. take $a=b=1$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.